A reengenharia do ensino das engenharias: da construção do discurso oficial à construção de reformas curriculares - Eduardo Marques Arantes (2002)
The aim of the present thesis is to analyze de Reengenharia do Ensino das Engenharias since the Programa REENGE development till the curricula reform in two engineering colleges. The research has been carried out into a sociological perspective based on the Nova Sociologia da Educação and the Teoria Crítica de Currículo theory, and combined with the pedagogical principle model by Basil Bernstein that enables us to study educational reforms. In order to gather the data, the methodological approaches were observation, interviews and documents analysis. The empirical search is divided into three parts. The first one examines the Programa REENGE development: its origin, its purpose, and the discussions that took place before the project implementation in the Engineering colleges, in general. The second one analyzes the reform in the college A and B: the project of the colleges, their connection with REENGE, the oppositions and the conflicts. The third one refers to the case study of the course reform of the A Civil Engineering College: the curriculum continuities and ruptures, and the differences between the projected curriculum and the implemented one. As regards the teachers´s formation in the colleges researched, the study reveals that it is necessary to promote a process that allows the curriculum critical analysis.